2018
DOI: 10.1021/acscentsci.8b00130
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO Production by Photoelectrochemical Methane Oxidation on TiO2

Abstract: The inertness of the C–H bond in CH4 poses significant challenges to selective CH4 oxidation, which often proceeds all the way to CO2 once activated. Selective oxidation of CH4 to high-value industrial chemicals such as CO or CH3OH remains a challenge. Presently, the main methods to activate CH4 oxidation include thermochemical, electrochemical, and photocatalytic reactions. Of them, photocatalytic reactions hold great promise for practical applications but have been poorly studied. Existing demonstrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 64 publications
1
53
0
Order By: Relevance
“…Over the past several decades, various semiconductors have been employed for constituting such a PEC system [11, 12] . Among them, tungsten oxide (WO 3 ) has been known as one of the most promising candidates because of its non‐toxicity, high oxidation ability and suitable band gap [8, 13] .…”
Section: Figurementioning
confidence: 99%
“…Over the past several decades, various semiconductors have been employed for constituting such a PEC system [11, 12] . Among them, tungsten oxide (WO 3 ) has been known as one of the most promising candidates because of its non‐toxicity, high oxidation ability and suitable band gap [8, 13] .…”
Section: Figurementioning
confidence: 99%
“…Very recently, a new PEC approach for CH 4 oxidation to CO over Ti 3+ doped atomic-layer-deposition-grown TiO 2 has been reported for the CO production with over 80% selectivity in all products (CO, O 2 , and carbonate, etc.). 39 Details of typical activities can be found in Table 1. It is extremely promising that, using sunlight without any further energy, CH 4 can be directly converted into high-value products, although the reaction rate is still several orders of magnitude lower than thermally catalyzed processes.…”
Section: Solar and Thermally Catalyzed Small-molecule Conversionmentioning
confidence: 99%
“…Han et al reported that (001)‐terminated TiO 2 nanosheet exhibits an excellent photocatalytic activity, which is even better than commercial Degussa P25 TiO 2 . It is noteworthy that apart from widely investigated photocatalytic water splitting, 2D TMOs are emerging as promising photocatalysts for other value‐added chemical reactions in recent years . For instance, Chen et al synthesized ultrathin, single‐crystal WO 3 nanosheets by 2D oriented attachment .…”
Section: Potential Applications Of 2d‐tmosmentioning
confidence: 99%
“…They found that the dimensionality reduction alters the bandgap of WO 3 such that the WO 3 nanosheet becomes active in the photocatalytic reduction of CO 2 into CH 4 in the presence of water. More recently, Li et al discovered that on anatase (101)‐terminated TiO 2 , CO can be produced via photocatalytic oxidation of CH 4 with a remarkably high yield of 81.9% . They proposed that such high selectivity for CO formation stems from the existence of surface Ti 3+ sites.…”
Section: Potential Applications Of 2d‐tmosmentioning
confidence: 99%